Professoralidade de bacharéis em matemática: trajetórias e experiências docentes no ICEN/UFPA - Patricio, Rafael Silva (2024)
This thesis sought to understand the constitution of the professorship of university teachers with a bachelor's degree in mathematics. To this end, it aimed to find out, through their narratives, their trajectories and experiences in the professional and/or personal sphere that contributed to the construction of their professorship. The specific objectives were: to identify which aspects of the training path contributed to the constitution of the professorship of these professionals; to analyze, based on their answers, characteristics that permeate the constitution of the professorship of these bachelors; and, to establish possible links between the constitution of professorship, the training path and professional performance. For theoretical support, we drew mainly on the publications of: Bolzan (2001; 2002; 2006; 2007; 2016; 2019), da Cunha (2018), Freitas (2000; 2002), Isaia (2003; 2008) and Powaczuk and Bolzan (2009). The methodological approach was qualitative and sociocultural in nature, in which data was collected through semi-structured interviews and analyzed using the content analysis technique, based on the framework proposed by Bardin (2006). The participants in this research were four teachers with a bachelor's degree in mathematics, who are permanent lecturers at the Federal University of Pará (UFPA) and have extensive teaching experience. This audience was chosen because, following the bibliographic survey carried out between 1990 and 2020, which found more than 1,400 mentions of the term professorality, many of them used Pereira (1996) as their main reference, but none of the studies targeted teachers with a bachelor's degree in mathematics. In this way, we gave a voice to these teachers, in which we were able to learn about their formative paths, work experiences, particular values and their own reflections on the act of teaching and learning mathematics. Their most representative statements were categorized and, when there were similarities, they were grouped together until we reached the final categories. These were: trajectory, self-reflective aspect, experience and sociocultural aspect. We defined each of these categories and, after analyzing them, we could see that they are part of the constitution of the professorship of each of the teachers taking part in this research. We also noticed that there was a behavioral change in each of the teachers over the course of the construction of this professorship. The results showed that this change occurred mainly in their treatment of their students, their commitment to their studies, their awareness, their decision-making, their wisdom and their more flexible behavior.